Hybrid Co3O4@Co9S8 Electrocatalysts for Oxygen Evolution Reaction - Tong, Yong-Li; Xing, Lei; Dai, Mei-Zhen; Wu, Xiang (Frontiers in Materials, 2019)
It is very essential to design an efficient and low-cost electrocatalyst for oxygen evolution reaction (OER). In this work, we report synthesis of Co3O4@Co9S8 heterostructures (Co-HSs) by employing Co3O4 nanowires (Co-NWs) as the precursor on nickel foam though a facile hydrothermal method. The unique structures can combine the advantages of one-dimensional nanowires and two-dimensional nanosheets, simultaneously, which possess plentiful defect atoms and active sites. The as-prepared Co-HSs exhibit excellent electrocatalytic performance for OER, which present a low overpotential of 80 mV at 10 mA cm-2 during OER process and small Tafel slope of 107.2 mV dec−1.